Europe at the Crossroads - Zielonka, J; Brittan, L; Hannay, D (2009)
Looks at the growing disillusionment with the EU in the minds of the citizens of Europe, the steady erosion of the `permissive consensus’ on Europe, and an over-preoccupation with institutional engineering. Such a preoccupation ignores the concerns of people as embodied in politics, economics and culture, and leads inevitably to a loss of legitimacy in which elites are increasingly detached from the electorate.